Sayap Garuda in Sarawak and Sabah after the Second World War until the 1950s - Suffian Mansor (IHiS (Indonesian Historical Studies), 2019)
Interaction among the islands in the Malay archipelago in early period was through trade, culture and brotherhood. This relationship persisted despite Western powers trying to set-up Western-style of political boundaries to justify their terrirorial claims in the archipelago. This is also the case between British dominions in Borneo namely Sarawak and Sabah with the Dutch domination in Indonesia. It was revealed that this past relationship was feared by the colonial powers after World War II. This is because of the liberation movement and anti-colonial movement in  Indonesia. Meanwhile, Indonesia's independence movement worried the British who had just colonized Sarawak and Sabah. Both regions were also experiencing political changes that began to counter British rule in Sarawak and Sabah. Although the opposition differed between the two territories, their original purpose was to free themselves from British occupation. Of particular concern to the British was the nationalist movement in Indonesia which was feared to influence political movements in Sarawak and Sabah. This is clearly demonstrated by the presence of several active Indonesian organizations in Sarawak and the existence of political movements in Sabah that supported Sukarno and Hatta. The British tried to stop the Indonesian influence from working in these two territories. The purpose of this article is to look at aspects of cultural space that have long been involved in political movements in Sarawak and Sabah. This article uses a content analysis approach using primary sources from London and secondary materials from libraries in Malaysia. From this point of view, we can make a clear finding that friendship and brotherhood are strong in the archipelago despite the fact that Western powers are trying to separate them.